Socializing Halal Certification Guidelines for MSMEs in Pucangan Village, Kartasura District, Sukoharjo Regency - Nurkholish Majid; Angga Dwi Prasetyo (MITRA: Jurnal Pemberdayaan Masyarakat, 2021)
The halal certification is important to ensure the public and business owners regarding halal products. However, the implementation of the halal certification program has faced some problems, such as the lack of facilitation for Micro, Small, and Medium Enterprises (MSMEs) and the high cost of halal certification. This activity is to socialize the importance of halal certification and provide assistance regarding the procedures and documents required in obtaining the halal certification. This activity targets the MSMEs actors who have their businesses around the IAIN Surakarta College and was carried out by socializing halal certification to the participants. During the preparation phase, we examine the participants’ understanding of halal product assurance and looked for information about the procedures of obtaining halal certification from LPPOM MUI and BPJPH. Th socialization activity was carried out in one day at Gedung Pusat Pengembangan Bahasa IAIN Surakarta. The certification guidelines socialization was attended by MSMEs owners around the IAIN Surakarta College. Based on the pretest and posttest results and the enthusiasm of the participants during the question-answer session, we could conclude that the activity has met our goals. This activity will benefit the MSMEs owners around IAIN Surakarta College in developing halalan toyyiban products’ assurance.